Indirect causatives in Basque: The syntax of implicit causees - Berro, Ane; Odria, Ane; Fernández, Beatriz (Natural language and linguistic theory, 2025)
In Basque there is a morphological causative construction where the causative suffix is added to the verbal root and an additional argument—the causer—is added to the already existing ones. In this paper we analyze indirect causatives (ICs), that is, morphological causative constructions where the causee—the caused-to-act subject—is left implicit, with no morphological reflex. Our analysis argues that both causative constructions, the direct and the indirect ones, involve a Voice-over-Voice projection and discusses its consequences for Case and Agreement. Additionally, we explore the nature of the implicit causee, and claim that it is syntactically projected as a strong implicit argument but with deficient φ -features. In these respects, it is similar to the impersonal subject found in Basque. Nevertheless, it differs in one key aspect: the causee is projected in a phrase with its own probe, resulting in distinct behavior concerning the PCC. This paper contributes to the discussion on the different versions of Voice, the syntactic nature of implicit arguments and how they interact in different constructions like causatives and impersonals.